Przyznanie się oskarżonego do winy w rzymskim procesie karnym - Chmiel, Andrzej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
During the whole period of the Roman Republic until the second century AD, defendant’s confession was regarded as a sufficient basis for conviction in the Roman criminal procedure. This approach resulted mostly from the fact that the perpetrator’s act was viewed only from the perspective of its effects and not the defendant’s motives. Only during the Roman Empire period confessio came under the supervision of first the Caesar himself and then his officials. During the Principate period, a judge, whose role was fulfilled by a Caesar’s official, was granted certain tools which were supposed to help him find out the truth. These tools were tormenta. It seems that the introduction of torture forced especially the Roman jurisprudence to become interested in the problem of the perpetrator’s guilt and also in psychological evaluation of credibility of the culprit’s testimony. Consequently, it was due to tormenta that confession ceased to be regarded as regina probationum in the Roman criminal procedure.